A Systematic Review of Digital and Computer-Based Alcohol Intervention Programs in Primary Care - K. Nair, Natasha; C. Newton, Nicola; Shakeshaft, Anthony; Wallace, Paul; Teesson, Maree (Current Drug Abuse Reviews, 2015)
Background. Alcohol misuse is a significant public health issue resulting in substantial morbidity, premature mortality and costs to the healthcare system. Although face-to-face interventions offered by health practitioners have been shown to be effective, they are not routinely offered due to lack of time, training and resources, and potential damage to rapport. Computerbased interventions may help overcome these implementation barriers. Approach. Suitable research databases were searched and studies were selected if they described digital or computer-based alcohol interventions used by primary care patients. Studies which did not report patient alcohol outcomes were excluded. Key findings. Fifteen trials were identified, eleven of which trialled brief interventions only while the remaining four trialled both brief and extended interventions. Nine trials were associated with a reduction in alcohol use at followup. Conclusion. This is the first systematic review of digital or computer-based alcohol intervention programs used by primary care patients. Although the number of trials in this area of research is relatively small, their findings indicate effectiveness in reducing alcohol consumption as well as drinking related consequences. Extended interventions which offer additional opportunities to monitor drinking over time appear no more effective than single occasion brief interventions. These findings suggest that digital and computer-based interventions in primary care may have the potential to increase alcohol intervention activities in the general population at a relatively low cost and low burden on practitioners.
Keywords: online